Using narrative in research - Bold, Christine (Los Angeles ; London : Sage, 2012)
"Serving as an introduction to narrative methods and narrative analysis, Christine Bold's new book provides students, researchers, and other professionals with an introduction to the theory and practice of narrative approaches in research. This book provides clear coverage of the informing theories and principles that underpin narrative traditions and offers the reader guidance on the main methods of collecting and analyzing narrative data. This book does everything that a methods book needs to do. It is practical, yet sets out the theory and history behind the approach, and it looks explicitly at design, ethics, data gathering, data analysis and writing as an ongoing process of narrative research. Bold's text deals comprehensively with conceptual issues within narrative research and is driven throughout by a range of real research specific examples of narrative analysis in action. This is an ideal text for any student, researcher or professional interested in understanding and using narrative in research and analysis; it practical, example-driven coverage is ideally suited to those new to the field"--Publisher description.
1. Narrative Beginnings : Autobiography, Biography and Fiction -- 2. What Is Narrative? -- 3. Designing Research Projects with a Narrative Approach -- 4. Ethics and a Narrative Approach -- 5 Narrative Thinking : Provoking and Sustaining Reflective Thought -- 6. Collecting Narrative Data -- 7. Analyzing Narrative Data -- 8. Representative Constructions in Narrative Analysis -- 9. Reporting Narrative Research.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Narrative inquiry (Research method); Electronic books